The Effects of Local Police Surges on Crime and Arrests in New York City - Fagan, Jeffrey (PLOS ONE, 2016)
Operation Impact was a policing strategy that deployed extra police officers to high crime areas in New York City known as impact zones. Officers were encouraged to conduct investigative “street” stops of citizens suspected of either felony or misdemeanor crimes in these areas. City officials have credited the program as one of the leading factors for New York City’s low crime rate. We rely on difference-in-difference regressions to estimate the effect of Operation Impact on reported crimes and arrests from 2004-2013. Both stops and arrests increased in impact zones. Arrests for weapons and other felony offenses increased in impact zones, as did investigative “street” stops. We find that the increase in “street” stops in impact zones was associated with a small reduction in overall crime and large reductions in burglary offenses. The increase in stops based on indicia of suspicious behavior or actions alone in impact zones had no measurable effect on crime. In contrast, an increase in stops in impact zones based on probable cause or indicia of actual crime was associated with significant crime reductions. The results suggest that Operation Impact contributed marginally to overall crime reductions but generated a high volume of unproductive police stops that had little crime reduction benefit. The findings raise fundamental questions about due process safeguards when the police saturate areas and engage in aggressive stop practices in an effort to reduce crime